2-Substituted-1-(2-morpholinoethyl)-1H-naphtho[2, 3-d]imidazole-4, 9-diones: Design, synthesis and antiproliferative activity. Issue 14 (1st August 2018) - Liu, Zhanxiong; Zhang, Zhenfeng; Zhang, Wanbin; Yan, Deyue
Graphical abstract: Highlights: 2-Substituted-1-(2-morpholinoethyl) naphthoquinone imidazoles as antitumor drugs. Good cytotoxicity was observed against MCF-7, Hela and A549 cell lines. Good selectivity was observed against L929 cell line. Abstract: Thirty-six of novel compounds 2-substituted-1-(2-morpholinoethyl)-1 H -naphtho[2, 3- d ]imidazole-4, 9-diones, bearing a N -(2-morpholinoethyl) group and a 2-substituted imidazole segment on a naphthoquinone skeleton, were designed, synthesized and tested as anticancer agents. Cytotoxicity was evaluated in vitro against three human cancer cell lines: human breast carcinoma cell line (MCF-7), human cervical carcinoma cell line (Hela), and human lung carcinoma cell line (A549); and one normal cell line: mouse fibroblast cell line (L929). Among them, the compound 2-(3-chloro-4-methoxyphenyl)-1-(2-morpholinoethyl)-1 H -naphtho[2, 3- d ]imidazole-4, 9-dione showed good antiproliferative activity against MCF-7, Hela and A549 (IC50 values are equal to 10.6 μM, 8.3 μM and 4.3 μM respectively) and low cytotoxicity to L929 (IC50 value is equal to 67.3 μM).